2017
DOI: 10.1093/rheumatology/kex044
|View full text |Cite|
|
Sign up to set email alerts
|

The potential overlapping populations for treatment with belimumab and rituximab using current NHS England and National Institute for Health and Care Excellence Guidelines in England and Wales

Abstract: Running Title Belimumab use in Refractory SLEKey Words Systemic Lupus Erythematosus, Biologic Therapy, Rituximab, Belimumab, Register. We sought to investigate the number of patients and the clinical characteristics of patients treated with a biologic in the BILAG-BR who would potentially have been eligible for belimumab using this guidance [5] Of the 270 patients registered for biologic use to Nov 2015, 82 (33%) had evidence of both low complement and elevated anti-dsDNA antibodies at enrolment. Of these, 46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The B cell activating factor (BAFF)neutralizing monoclonal antibody belimumab was the first biologic licensed for the treatment of lupus following two large phase III clinical trials, BLISS 52 (21) and BLISS 76 (22), and has recently been shown to be effective for renal lupus (23). However, the limited criteria permitting the use of belimumab treatment in England (4), based on an assessment by National Institute for Clinical Excellence which takes into account therapeutic benefit and cost effectiveness, results in far fewer patients with active, refractory disease receiving belimumab compared to rituximab (24).…”
Section: Introductionmentioning
confidence: 99%
“…The B cell activating factor (BAFF)neutralizing monoclonal antibody belimumab was the first biologic licensed for the treatment of lupus following two large phase III clinical trials, BLISS 52 (21) and BLISS 76 (22), and has recently been shown to be effective for renal lupus (23). However, the limited criteria permitting the use of belimumab treatment in England (4), based on an assessment by National Institute for Clinical Excellence which takes into account therapeutic benefit and cost effectiveness, results in far fewer patients with active, refractory disease receiving belimumab compared to rituximab (24).…”
Section: Introductionmentioning
confidence: 99%
“…One study was excluded as it was a corrigendum of another study. 12 Two other studies 15 , 17 were excluded for not reporting on SLE patients and three 8 , 9 , 12 were excluded as they did not report on patient clinical outcomes. Reviewing the references of the 5 remaining publications, one additional study which met our criteria was identified.…”
Section: Resultsmentioning
confidence: 99%
“…After applying the inclusion and exclusion criteria, 11 studies 8–17 were selected. One study was excluded as it was a corrigendum of another study.…”
Section: Resultsmentioning
confidence: 99%
“…Although countless open-labeled studies and their metanalyses indicated that rituximab was effective, it failed to demonstrate efficacy in two randomized controlled trials for SLE ( Li et al, 2022 ). Notwithstanding these mixed results, rituximab remains the most widely used targeted therapy for SLE in England ( McCarthy et al, 2017 ), though its availability and use around the world varies. In one study, SLE was the commonest diagnosis for off-label use of rituximab ( Sarsour et al, 2020 ).…”
Section: Rituximab For Sle: the Most Controversial Drug In The Histor...mentioning
confidence: 99%